DETERMINATION OF THE DEGREE OF SHEEP INFESTATION WITH MONIEZIOSIS IN THE CENTRAL REGIONS OF UZBEKISTAN - X.A, Safarov; Sh.A, Djabbarov; K.Sh, Akramov (Research Focus International Scientific Journal, 2026)
This article presents information on the prevalence of monieziosis in sheep specifically the extent of invasion, in the Samarkand and Jizzakh regions of the Republic of Uzbekistan. According to the obtained results, monieziosis was detected in 11.0% of the examined sheep in the Samarkand region, whereas in the Jizzakh region the prevalence rate was 11.2% of the investigated animals.